Antibiotic bioremediation by new generation biochar: Recent updates. (August 2022) - Patel, Anil Kumar; Katiyar, Ravi; Chen, Chiu-Wen; Singhania, Reeta Rani; Awasthi, Mukesh Kumar; Bhatia, Shashikant; Bhaskar, Thallada; Dong, Cheng-Di
Graphical abstract: Highlights: Antibiotic pollution enables evolution of multi-drug resistant pathogenic microbes. Microbial degradation of antibiotics is challenging due to antimicrobial activity. Engineered biochar offers more effective remediation of wide antibiotic pollutants. Heteroatom doping determined as an efficient approach for effective remediation. The removal efficiency of antibiotics is ranging 13–552 mg g −1 by various biochar. Abstract: The evolving multidrug resistance in microbes with increasing antibiotic pollution is becoming a severe global crisis. Recent developments on antibiotic remediations by biochar are promising. Advancements in biochar engineering enhanced biochar remediation efficiency to another level through developing new interactions and bonding abilities with antibiotic pollutants. Especially chemical/metal-composite modification significantly increased catalysis of biochar. The review's main focus is to underline biochar efficiency for the abatement of emerging antibiotic pollutants. Moreover, to relate feedstock, production conditions, and engineering techniques with biochar properties. Also, modification strategies are reviewed to obtain biochar or their composites before examining improved remediation potential ranging from 20 to 552 mg g −1 for various antibiotics. Biochar offers different interactions depending on the surface functionalities e.g., π-π stacking, electrostatic, H-bonding, etc. Biochar and related composites have also been reviewed for remarkable properties e.g., photocatalysis, adsorption, and oxidation processes. Furthermore, future research directions and opportunities for biochar research are discussed.